Internal Determination of Profitability of Commercial Banks Operating in Pakistan - Dr Javed Meraj; * Usama Rasheed; Kannar Ibrahim; Qambar Jan; Abid Ali; Pervez Ahmed (Review Journal of Social Psychology & Social Works, 2024)
The research examined the internal factors impacting the profitability of 15 commercial banks operating in Pakistan. We have taken 10 years’ data of selected banks from the time period 2014 to 2023. We used Return on Assets (ROA) as our dependent variable while Debt to Assets (DTA), Deposits to Assets (DPTA), Equity to Assets (ETA) and Bank Size (LTA) are taken as independent variables. The research discusses around quantitative approach with the help of secondary data from the financial statements and State Bank of Pakistan websites of the selected banks. Data were analyzed using multiple statistical tests and methods to evaluate the internal elements affecting commercial banks profitability. Descriptive statistics shows significant variation in profitability and financial structure across banks. Correlation reveals weak positive relationship between ROA and both DPTA (0.1645) and DTA (0.1390), showing that greater reliance on deposits and debt marginally enhance profitability. While a weak negative correlation among ROA and LTA (-0.1507) suggests minor profitability issues for larger banks. Regression Analysis point out that internal factors limited explanatory capacity, with bank size showing a statistically significant negative effect. The study concludes that while internal factors affect profitability, external factors outside the banks like market conditions, economic policies or more also impact the profitability. Therefore, further research is needed to investigate the external influence.